Asupan Zinc Berpengaruh pada Stunting Balita : Studi Belah Lintang pada Balita Usia 3 Tahun : Zinc Intake Affects Toddler Stunting: A Cross-Sectional Study on Toddlers Aged 3 Years - Sri Priyantini; Anisa Nurmalitasari; Masyhudi AM (Universitas Airlangga, 2023)
Background: Stunting toddlers in Indonesia was still a concern of the government. The Indonesian Ministry of Health noted that the 2020 stunting rate was 27.7% to 24.4% in 2021, while the government's target in 2024 was 14%. Objectives: The purpose of the study was to prove the relationship between Zinc intake and the average height growth of toddlers, in addition to proving the relationship between Zinc intake and stunting. Methods: A cross-sectional study was conducted on 54 toddlers with a history of births at Sultan Agung Hospital and Bangetayu Health Center in August-November 2017. The average body length growth was the rate of body length increase per month for the first three years of life (cm/month). Data on Zinc intake (mg/day) were obtained from food recall with a food model and analysis of Zinc content in food using the Nutrisurvey application. Test the hypothesis statistically using Spearman, Chi-square, and Fisher's Exact. Results: Zinc intake was not correlated with mean height growth (p=0.231 r=0.166). Stunting was significantly associated with Zinc intake <3 mg/day, p=0.001. There was a relationship between nutritional status WAZ-score and stunting at three years, p = 0.001. There was a negative correlation between birth length and average height growth. Conclusions: Zinc intake was not associated with the rate of growth in body length in the first three years. Daily Zinc intake was associated with stunting in toddlers.